The life and death of images : ethics and aesthetics - Costello, Diarmuid; Willsdon, Dominic (London : Tate Publishing, 2008)
From the 1970s to the early-1990s, the discourse surrounding aesthetics disappeared from the study of art history, theory and cultural studies. Claims for the aesthetic value of art-works were thought of as elitist and politically regressive. This work considers this aesthetics, demonstrating its cross-disciplinary relevance.
Onderzoek KASK (1KA-OFVR)
boek